2021
DOI: 10.3390/cancers13215371
|View full text |Cite
|
Sign up to set email alerts
|

A Mass Spectrometry Imaging Based Approach for Prognosis Prediction in UICC Stage I/II Colon Cancer

Abstract: Currently, pathological evaluation of stage I/II colon cancer, following the Union Internationale Contre Le Cancer (UICC) guidelines, is insufficient to identify patients that would benefit from adjuvant treatment. In our study, we analyzed tissue samples from 276 patients with colon cancer utilizing mass spectrometry imaging. Two distinct approaches are herein presented for data processing and analysis. In one approach, four different machine learning algorithms were applied to predict the tendency to develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…From the analysis of the most relevant m / z features for the classification, as calculated by forward feature extraction, we can conclude that COL1A1, COL1A2, and COL3A1 play a central role in tumor progression. As also indicated by other studies, collagen content can impact the progression of tumors with different origins [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ], which can likely be attributed to the role of collagen in cellular migration and tumor progression [ 35 , 36 ]. Moreover, in PDAC, collagens have been associated with poor prognoses [ 37 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 67%
“…From the analysis of the most relevant m / z features for the classification, as calculated by forward feature extraction, we can conclude that COL1A1, COL1A2, and COL3A1 play a central role in tumor progression. As also indicated by other studies, collagen content can impact the progression of tumors with different origins [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ], which can likely be attributed to the role of collagen in cellular migration and tumor progression [ 35 , 36 ]. Moreover, in PDAC, collagens have been associated with poor prognoses [ 37 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 67%
“…Some proteomic studies have also shown that protein expression varies in different CRC tumor zones 48 . The only other MALDI imaging study of CRC liver metastasis was able to show functional and therapeutic biomarker heterogeneity in peritumoral, rim and center zones of metastatic tumor tissues 27 . Data from different in-vivo cancer models show functionally different zones in several tumors: proliferation at the outer zone, differentiation in the middle zone, and central cell death 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus MALDI imaging is a predestined technique for the proteomic investigation of the tumor microenvironment and intratumor heterogeneity in complex tumor tissues 24 . Tryptic peptide imaging was applied to CRC for the discovery of protein profiles associated with clinical marker 25 , diagnosis 26 , prognosis 27 and presence of lymph node metastases 28 . Turtoi et al applied MALDI imaging to analyze spatial proteomic heterogeneity in liver metastasis of CRC.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding microsatellite instability (MSI), a screening study of deficient mismatch repair profiles on colorectal cancer distribution in Romania by Lungulescu showed that MSI status does not carry a significant prognostic role [ 70 ]. Apart from clinical and pathological factors, new insights regarding the role of genetic [ 71 ], transcriptomic [ 72 ] and mass spectrometry imaging proteomics analysis [ 73 ] as prognostic instruments are still under investigation concerning the influence upon clinical decision in loco-regional recurrence prediction. Additionally, immunohistochemical expression of the REG4 proteins, frequently detected in right colon cancer, was significantly correlated with low recurrence-free survival [ 74 ].…”
Section: Discussionmentioning
confidence: 99%